Pengaruh Positif Implementasi Kurikulum Merdeka pada Pembelajaran Anak di Ra An-Nur - Rismayanti Dewi; Ageng Saepudin Kanda S (Universitas Maritim AMNI Semarang, 2024)
One of the most important and often overlooked parts of education is the curriculum. The implementation of an independent curriculum program is demonstrated by the success of teachers and students who are able to contribute to learning success through collaboration. The purpose of this study is to determine the positive effects of the implementation of an independent (independent) curriculum on learning in RA Anna School in order to improve the implementation of the independent curriculum and make learning more enjoyable and comfortable. and to determine this learning objective. The research is to achieve qualitative methods combined with descriptive methods. The outcome of this discussion will be to encourage children to learn skills that contribute to their overall development, such as critical thinking, creativity, and social skills. By paying attention to children's interests and needs, you can increase their engagement and motivation.